2003
DOI: 10.1128/mcb.23.7.2451-2462.2003
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Poly(ADP-Ribose) Polymerase 1 and Poly(ADP-Ribosyl)ation in Regulation of Centrosome Function

Abstract: The regulatory mechanism of centrosome function is crucial to the accurate transmission of chromosomes to the daughter cells in mitosis. Recent findings on the posttranslational modifications of many centrosomal proteins led us to speculate that these modifications might be involved in centrosome behavior. Poly(ADPribose) polymerase 1 (PARP-1) catalyzes poly(ADP-ribosyl)ation to various proteins. We show here that PARP-1 localizes to centrosomes and catalyzes poly(ADP-ribosyl)ation of centrosomal proteins. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
99
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 64 publications
15
99
1
1
Order By: Relevance
“…Our data also revealed centrosome amplification in about 25% of Parp1 À/À MEFs. This observation is consistent with a previous finding that absence of Parp1 causes centrosome hyperamplification, 25 and it provides a basis for the elevated centrosome number in the Brca1 D11/D11 ;Parp1 þ /À MEF.…”
Section: D11/d11supporting
confidence: 82%
“…Our data also revealed centrosome amplification in about 25% of Parp1 À/À MEFs. This observation is consistent with a previous finding that absence of Parp1 causes centrosome hyperamplification, 25 and it provides a basis for the elevated centrosome number in the Brca1 D11/D11 ;Parp1 þ /À MEF.…”
Section: D11/d11supporting
confidence: 82%
“…At least two other centrosomal proteins Cep76 [22] and Cep170 [23] contain RXXPDG TNKS1 binding sites and a number of other centrosomal proteins contain degenerate motifs, raising the possibility that TNKS could regulate stability of additional centrosomal proteins. Previous studies have demonstrated localization of other PARPs (PARP1 [24] and PARP3 [25]) to interphase centrosomes and PARP1 was found to be required for maintenance of proper centrosome number [26]. Hence, PARsylation (through multiple PARPs and targets) may have a general role in centrosome function.…”
Section: Resultsmentioning
confidence: 98%
“…The failure to remove PAR from either covalently modified proteins or noncovalently bound PAR may lead to growth arrest and cell death, because many PAR-modified proteins are important for cell survival and DNA processing͞repair (37)(38)(39)(40)(41). Recent evidence suggests that poly-(ADP-ribosyl)ation regulates transcription (5) and that the failure to degrade PAR polymer may lead to transcriptional dysregulation.…”
Section: Discussionmentioning
confidence: 99%